Making a difference in women's lives? : case study of women's empowerment programme in Rajasthan - Taipale, Jenni (2015)
The study is placed in an Indian NGO working for women’s empowerment by the means of informal education, vocational trainings and awareness-raising activities. The goal is to find out to what extent this NGO managed to reach gender justice in practice. The evaluation answers to the questions of what the understanding of gender equality and empowerment was among the people working for the NGO, what the conditions of the chosen participants were and how they influenced participation and then how successful the NGO was in terms of changing gender division of labour and women’s cultural value. My theoretical framework is focused on the Empowerment (GAD) approach, and the gender planning framework of Caroline Moser is used as the basic foundation with its tools of gender analysis and gender needs assessment. However, this will be used with the emphasis on the two-dimensional conception of gender (Nancy Fraser) and on the transformatory potential (Kate Young and Saskia Wieringa). In addition to these points, the issue of intersectionality will also be addressed because gender inequality is strengthened by the additional challenges in the women’s lives. The contextual component follows throughout the evaluation. The study is done as an ethnographic case study evalution.The data consists of observations done at the NGO between November 2011 to April 2012, by survey interviews done at Kathputli Nagar in Jaipur with 17 of the NGO’s chosen participants, and by analysing organizational documents and website. The analysis is completed with the help of a simple logic model (resources, activities, immediate results). Based on my research, I argue that the transformatory potential of the NGO programme is greater in improving women’s cultural value (self-esteem, decision-making power) than in challenging the gender division of labour (occupational segregation, women’s sole responsibility over housework and childcare). In many ways the gender division of labour was taken for granted leading to helping women to cope with what they are already doing instead of creating new ways of challenging unequal structures. Due to the different additional issues present in the participants’ lives, it became also clear that there is a need for greater role of the state in supporting the basic needs of the people together with additional focus on the specific gender concerns of the women